Nonuniform piecewise membership function approximation methods based robust tracking control design of T‐S fuzzy systems - Xie, Wen‐Bo; Xu, Bo‐Lin; Peng, Chen; Zhang, Jian (International journal of robust and nonlinear control, 2022)
For the stability analysis issue of a T‐S fuzzy system, improved piecewise membership functions dependent approach is proposed to reduce conservatism. Based on a least‐square method, the nonlinear membership functions are approximated by a series of decoupled polynomial functions. Then the piecewise vertices are chosen by a newly proposed derivative‐integral nonuniform division approach. For the robust tracking control task, a series of convex robust stable conditions are obtained. Finally, a mass‐spring‐damper (MSD) simulation example is adopted to illustrate the effectiveness of the designed method.